(untitled) (Journal of actual problems of jurisprudence, 2016)
This article analyzes the category subekta crime under Islamic law. Particular attention is paid to such characteristics of the perpetrator, as age and responsibility. These features are crucial. Emphasizes that under Islamic law there is no definition of the perpetrator. Characteristic for the Muslim criminal law is a fact, as the preservation until today unequal legal status of women and men as perpetrator and the victim of the crime.